1992
DOI: 10.1111/j.1600-0528.1992.tb01702.x
|View full text |Cite
|
Sign up to set email alerts
|

Remaining teeth, oral dryness and dental health habits in middle‐aged Norwegian rheumatoid arthritis patients

Abstract: The aim of the study was to assess the effect of rheumatoid arthritis (RA) upon dental health. A questionnaire was mailed to all seropositive rheumatoid arthritis (RA) patients aged 44-56 yr in the files of the two main departments of rheumatology in South Eastern Norway. Data were obtained from 125 patients, constituting 91% of the target group. The number of remaining teeth in these patients was not related to disease duration or physical dysfunction, whereas a relationship to prolonged use of medication for… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
23
0

Year Published

1999
1999
2018
2018

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 27 publications
(25 citation statements)
references
References 13 publications
2
23
0
Order By: Relevance
“…In another minor study29 ST was reduced in 30% of RA patients. The prevalence of oral SISY was 6% when spontaneously reported by RA patients,2 32% when recorded as responses to questions,9 and 53% in a study considering frequent and periodical symptoms together 10. Such different results may be partly explained by different approaches in the assessment of SISY.…”
Section: Discussionmentioning
confidence: 93%
See 1 more Smart Citation
“…In another minor study29 ST was reduced in 30% of RA patients. The prevalence of oral SISY was 6% when spontaneously reported by RA patients,2 32% when recorded as responses to questions,9 and 53% in a study considering frequent and periodical symptoms together 10. Such different results may be partly explained by different approaches in the assessment of SISY.…”
Section: Discussionmentioning
confidence: 93%
“…Ocular or oral sicca symptoms (SISY) in RA patients have previously been reported in 18–25%7 8 and 6–53%2 9 10 of the patients, respectively. In a recently published pilot study11 we found a high prevalence of SISY in RA patients, but also an association with xerogenic medication—that is, medication with the capacity to induce dryness, for example xerostomia.…”
mentioning
confidence: 95%
“…Periodontitis has also been found to be more severe in patients with RA, who exhibit greater alveolar bone loss [32]. In addition, disability of the extremities and reduced manual dexterity caused by RA may impair oral hygiene and increase the risk for periodontitis and tooth loss [33]. Manifesting high levels of cytokines, such as IL-1 β , IL-6, and TNF- α , periodontitis has an immunologic profile similar to that of RA and both diseases are associated with elevated concentrations of matrix metalloproteinases (MMPs) and low concentrations of tissue inhibitors of MMP (TIMPs) [13].…”
Section: Discussionmentioning
confidence: 99%
“…It has been hypothesized that PD is associated with subsequent development of RA, but studies on this association have reported conflicting results and no prospective study has been conducted. Two cross-sectional studies and a retrospective case-control study showed no association(6–8). Other studies have found a higher prevalence of PD and tooth loss among patients with existing RA(9–15).…”
Section: Introductionmentioning
confidence: 92%